Equitable access to sustainable healthcare services for children with autism - Meshal A. Sultan (BJPsych International)
This perspective article addresses the critical issue of equitable access to sustainable healthcare services for children with autism spectrum disorder (ASD). Despite the increasing prevalence of ASD globally, significant disparities persist in accessing appropriate healthcare services. The lack of comprehensive data on autism prevalence and incidence in many regions further exacerbates this challenge, hindering the development of targeted interventions and equitable resource allocation. This paper sheds light on barriers to equitable access, including geographical disparities, cultural stigma, communication barriers and inadequate training of healthcare providers. Strategies for achieving sustainable solutions are proposed, including the expansion of telehealth services, financial assistance programmes, competency training, community-based support programmes and investment in high-quality research. By addressing these challenges and implementing evidence-based interventions, we can work towards ensuring that all children with autism have access to the healthcare services they need for optimal development and well-being.